ANALISIS RISIKO GANGGUAN SALURAN PERNAFASAN PADA KEGIATAN PEMBUATAN BATAKO DI UD. FATIMAH, KOTA PADANG - Suksmerri Suksmerri; Erdi Nur; Mukhlis Mukhlis; Sari Arlinda; Lili Oktia Pratiwi (Politeknik Kesehatan Kemenkes Makassar, 2023)
Background: The activity of the brick industry has the potential to cause air pollution. One of the air pollutants that can be produced from the brick industry is dust with a size of 10 m or also known as Particulate Matter 10 (PM10). Particulate Matter (PM₁₀) is a hazardous substance that can cause various health problems. The purpose of this research is to conduct an Environmental Health Risk Analysis on Bricks Workers. Methods: The design used in this study is the Environmental Health Risk Analysis (EHRA) method. The sample in this study was an air sample measuring 10 micrometers and a worker sample of 6 workers. Result: The result of this research is that the concentration of PM10 at the milling point is 19.4 g/m3. At the point of imprinting is 20.5 g/m3. And at the point of combustion is 231 g/m3. Conclusion: Thus, the concentration of PM10 in the brick industry at the point of grinding and molding is still below the Quality Standard Value, while at the firing point it exceeds the Quality Standard Value of 75 g/m3 according to Government Regulation no. 22 the year 2021. As many as 83.3% experience symptoms of respiratory disorders and are at risk of lifetime exposure. Suggestions from this research are to use Personal Protective Equipment (PPE) in the form of a respirator (anti-dust mask) and to carry out administrative control by reducing the time and frequency of dust exposure. And also flush the dusty workplace so that flying dust can be reduced.